Occurrence of major geomagnetic storms and their relation with plasma parameters, interplanetary magnetic field parameters, and geomagnetic index during solar cycle 23: article / Nur Syaahidah Mustafa - Mustafa, Nur Syaahidah (2015)
A geomagnetic storm is a temporary disturbance of the Earth's magnetic field which is magnetosphere usually occurred due to a disturbance in the interplanetary magnetic field (IMF). There are many parameters that can play role in the form of geomagnetic storms. Some of the parameters do play significant role in disturbance time index (Dst) morphology while some do not play significant roles. In this study, some parameters were analyzed to see their roles in the Dst morphology and hence can indicate the parameters that can be used to predict the storms. Three major geomagnetic storms were observed during three phase of the solar cycle. This paper investigates the relationship that exist among the following interplanetary magnetic field (IMF) parameters: (Bz, By, Bt), and the geomagnetic index (GI): (Kp, Dst. Ap, Ae) alongside with the plasma parameters: (T, D, V) during major geomagnetic storms. In this study, major geomagnetic storms were indicated by Dst index below than -200nT. All the data were taken from OMNIWeb Data Explorer. The relationship between IMF parameters, GI, and plasma parameters with disturbance time index (Dst) was studied. The periods of minimum phases of solar cycle 23 are between 1996-1998 and 2004-2006 while maximum phase is during 2000-2001. A correlative study between the geomagnetic indices and the peak of various plasma and field parameters during major geomagnetic storms of solar cycle 23 also presented. From this study, it shows that some parameters used play moderate role (0.3 < r < 0.5) in Dst morphology and some do not play significant role.